Usefulness of three-dimensional image navigation system for evaluation of hepatic artery before living donor liver transplantation: a case report - Michinori Matsumoto; Shigeki Wakiyama; Hiroaki Shiba; Yuichi Ishida; Yoshiaki Kita; Katsuhiko Yanaga (Surgical Case Reports, 2017)
Abstract Background The evaluation of the hepatic vascular anatomy in living liver donors is increasingly being performed by three-dimensional (3D) computed tomography (CT) angiography. However, details of hepatic artery anatomy obtained by 3D CT angiography are not always superior to those obtained by angiography. Here, we report a case in which the 3D image navigation system helped to detect segment II, III, and IV arteries (A2, A3, and A4, respectively) that individually originated from the proper hepatic artery (PHA); this could not be detected by 3D CT angiography. Case presentation A 46-year-old man with end-stage primary biliary cirrhosis was admitted to our hospital for evaluation as a candidate for living donor liver transplantation. The patient’s younger sister, aged 43 years, was the only living donor candidate. The predicted left liver graft volume with the middle hepatic vein was found to be 403 mL using the region-growing method with 3D CT software. This volume was sufficiently large for the recipient because the standard liver volume of the recipient was 1095 mL. 3D CT angiography was performed twice but could not reveal the anatomical structure of the left and middle hepatic arteries. However, simulation using the region-growing method demonstrated individual branching off of A2, A3, and A4 from the PHA; conventional angiography demonstrated the same results. Each branch was approximately 1 mm in diameter, which was too small for secure anastomosis. Therefore, we selected the right liver graft for simplicity. The postoperative course of the donor and recipient was uneventful, and they were discharged on postoperative days 10 and 46, respectively. Conclusions In conclusion, reconstruction of the hepatic vasculature using the 3D software by region-growing method might be a useful adjunct for surgical planning in the evaluation of the hepatic arteries in living liver donors.